Community college online learning administrators: how they make sense of their journey - DeKorte, Jodene, author; Quick, Don, advisor (Colorado State University. Libraries, 2008)
This study examined the journey of community college online learning administrators. A phenomenological approach was used to answer the primary question of what is the essence of the life and professional experiences that influenced these administrators in their work. Ten participants from across the country were interviewed in relation to their experiences as online learning administrators. Participants were chosen as those having two to ten years experience as an online learning administrators at a community college with a student body of no more than 15,000 students. Data was collected through two in-depth interviews using a broad open-ended question interview format. Analysis revealed that there were five main themes. First, barriers were the experiences or items that were difficult for the participants in their current position. Second, actions, were described as how the participants work in their current positions and how they see themselves leading. The third theme, observation of leadership, discusses what characteristics of leadership the participants have seen in superiors and how they view those people to be good or poor leaders. Fourth, working with groups, describes how the participants work with groups not only within their institutions but also within their community and state areas. Finally, current position, deals with the day-to-day details of the participants' jobs and their decision making process. One overarching phenomenon came out through all the main themes and subthemes, the essence of, people matter. Research of distance learning leadership is not as complete as other topics in administrative issues; more studies are needed around the connections from administrative actions to student success and what role administrators play. Additionally, a grounded theory study to determine a possible leadership style specifically focusing on the essence of people matter and online learning may help grow this area for future leaders. Finally, this study and further research may help community colleges in selecting the best candidates with the paramount skills for these types of positions for online learning.
Keywords: administrators; community college; leadership; online; online learning; community college education; school administration; distance learning; educational administration